Synthesis, Spectral, Thermal, Electrochemical, and Biocidal Activity of Tolyl/Benzyl Dithiocarbonates of Zinc(II). (24th December 2013) - Kalgotra, Nidhi; Gupta, Bhawana; Andotra, Savit; Kumar, Sandeep; Pandey, Sushil Kumar
Abstract : Tolyl/benzyl dithiocarbonates of zinc(II) [(o -, m -, p - CH3 C6 H4 and C6 H5 CH2 OCS2 )2 Zn] have been synthesized in 1 : 2 molar ratio by the reaction of zinc chloride, ZnCl2, with sodium salts of tolyl/benzyl dithiocarbonates( o -, m -, p - CH 3 C 6 H 4 O/ C 6 H 5 CH 2 O ) CS2 Na, in aqueous medium. These complexes were further reacted with nitrogen and phosphorous donor ligands to obtain donor stabilized complex of the type [[(o -, m -, p - CH3 C6 H4 and C6 H5 CH2 )OCS2 ]2 Zn. n L], (L = Bipy, Phen forn = 1 and PPh3, Py forn = 2 ). These complexes were characterised by elemental analysis, mass, IR, and NMR ( 1 H, 13 C, and 31 P) spectroscopies. The thermal analysis (TGA/DTA), cyclic voltammetry, and SEM have also been done. Distorted tetrahedral and octahedral geometries around the Zn(II) metal are proposed. These complexes have depicted potential antibacterial and antifungal activity.